Phascolarctobacterium wakonense sp. nov., isolated from common marmoset (Callithrix jacchus) faeces. Issue 7 (30th April 2019) - Shigeno, Yuko; Kitahara, Maki; Shime, Mari; Benno, Yoshimi
Abstract : Two strictly anaerobic strains (MB11 T and MB56) were isolated from common marmoset ( Callithrixjacchus ) faeces. Cells of the two strains were Gram-stain-negative, pleomorphic short (strain MB11 T ) or long (strain MB56) rods. Phylogenetic analysis based on 16S rRNA gene sequences revealed that both isolates were related to the genus Phascolarctobacterium . They had 16S rRNA gene sequences similarities lower than 93 % to previously described species, Phascolarctobacterium faecium ACM 3679 T and Phascolarctobacterium succinatutens YIT 12067 T, and 98.7 % between themselves. DNA–DNA hybridization values showed that strains MB11 T and MB56 were the same species. The genomic DNA G+C content of strains MB11 T and MB56 were 47.3–47.4 mol% and 47.7–48.0 mol%. The isolates had different enzymatic activities compared with P. succinatutens JCM 16074 T and different major cellular fatty acids compared with P. faecium ACM 3679 T . Substrate availability revealed that they utilized not only succinate, but also pyruvate. With pyruvate supplementation, they produced both propionate and acetate, while only propionate production occured with succinate. As suggested by the phylogenic and physiological properties of strains MB11 T and MB56, we propose the name Phascolarctobacterium wakonense sp. nov. with the type strain MB11 T (=JCM 32899 T =DSM 107697 T ).